Electron dynamics in a subproton‐gyroscale magnetic hole. Issue 9 (7th May 2016) - Gershman, Daniel J.; Dorelli, John C.; Viñas, Adolfo F.; Avanov, Levon A.; Gliese, Ulrik; Barrie, Alexander C.; Coffey, Victoria; Chandler, Michael; Dickson, Charles; MacDonald, Elizabeth A.; Salo, Chad; Holland, Matthew; et al.
Abstract: Magnetic holes are ubiquitous in space plasmas, occurring in the solar wind, downstream of planetary bow shocks, and inside the magnetosphere. Recently, kinetic‐scale magnetic holes have been observed near Earth's central plasma sheet. The Fast Plasma Investigation on NASA's Magnetospheric Multiscale (MMS) mission enables measurement of both ions and electrons with 2 orders of magnitude increased temporal resolution over previous magnetospheric instruments. Here we present data from MMS taken in Earth's nightside plasma sheet and use high‐resolution particle and magnetometer data to characterize the structure of a subproton‐scale magnetic hole. Electrons with gyroradii above the thermal gyroradius but below the current layer thickness carry a current sufficient to account for a 10–20% depression in magnetic field magnitude. These observations suggest that the size and magnetic depth of kinetic‐scale magnetic holes is strongly dependent on the background plasma conditions. Key Points: MMS data can resolve kinetic‐scale structure in space plasmas Agyrotropic electrons carry current in a subproton‐scale magnetic hole Current‐carrying electrons have gyroradii above the thermal gyro radius